Personality Disorder Diagnoses in Outpatient Forensic Mental Health: A Comprehensive Prevalence Study in the Netherlands - Barbera E. Van Reijswoud; Nikola Doubkova; Gina Rossi; Arno van Dam; Wiebren Markus; Kasia Uzieblo (Personality and Mental Health, 2026)
ABSTRACT Personality disorders (PDs) are associated with significant clinical and societal consequences and are highly comorbid with other psychiatric conditions. In forensic mental health settings, PD diagnoses are particularly relevant because they are linked to antisocial behavior, recidivism risk, and specific treatment needs. However, empirical knowledge about the prevalence of PD diagnoses in outpatient forensic mental health (OFMH) care is limited. We aimed to conduct a comprehensive study of the prevalence of PD diagnoses in OFMH institutions and to describe the demographic, clinical, and legal characteristics of individuals with PD diagnoses. Data were collected from OFMH institutions across the Netherlands for all adult individuals who received treatment in 2023. Fifteen institutions provided usable data, resulting in a total sample of 10,560 individuals. Descriptive analyses were conducted to estimate the prevalence of PD diagnoses and to examine differences across individual characteristics and treatment variables. Overall, 19.3% of all individuals were diagnosed with at least one PD. PD was the primary diagnosis in 12% of all individuals and an additional diagnosis in 7.3%, which seems to indicate that PD diagnoses are under‐recognized. The most frequently recorded specific PD diagnoses were other specified or unspecified PD, followed by borderline PD and antisocial PD. PD diagnosis prevalence was higher among female individuals, middle‐aged individuals, individuals receiving voluntary treatment, and those involved in more serious violent offenses. These findings provide large‐scale prevalence data on PD diagnoses in Dutch OFMH and highlight the importance of systematic assessment of personality pathology in forensic outpatient populations.